Aquaporin-4 antibodies in neuromyelitis optica and longitudinally extensive transverse myelitis. - Waters, P; Jarius, S; Littleton, E; Leite, M; Jacob, S; Gray, B; Geraldes, R; Vale, T; Jacob, A; Palace, J; Maxwell, S; Beeson, D; et al. (2008)
BACKGROUND: There is increasing recognition of antibody-mediated immunotherapy-responsive neurologic diseases and a need for appropriate immunoassays. OBJECTIVES: To develop a clinically applicable quantitative assay to detect the presence of aquaporin-4 (AQP4) antibodies in patients with neuromyelitis optica and to characterize the anti-AQP4 antibodies. DESIGN: We compared a simple new quantitative fluorescence immunoprecipitation assay (FIPA) with both indirect immunofluorescence and an AQP4-transfected cell-based assay, both previously described. We used the cell-based assay to characterize the antibodies for their immunoglobulin class, IgG subclass, and ability to induce complement C3b deposition in vitro. SETTING: United Kingdom and Germany. PARTICIPANTS: Serum samples from patients with neuromyelitis optica (n = 25) or longitudinally extensive transverse myelitis (n = 11) and from relevant controls (n = 78) were studied. MAIN OUTCOME MEASURES: Comparison of different assays for AQP4 antibodies and characterization of anti-AQP4 antibodies in patients with neuromyelitis optica. RESULTS: We found antibodies to AQP4 in 19 of 25 patients with neuromyelitis optica (76%) using FIPA, in 20 of 25 patients with neuromyelitis optica (80%) using the cell-based assay, and in 6 of 11 patients with longitudinally extensive transverse myelitis (55%) with both assays; these assays were more sensitive than indirect immunofluorescence and 100% specific. The antibodies bound to extracellular epitope(s) of AQP4, were predominantly IgG1, and strongly induced C3b deposition. CONCLUSIONS: Aquaporin-4 is a major antigen in neuromyelitis optica, and antibodies can be detected in more than 75% of patients. Further studies on larger samples will show whether this novel FIPA is suitable for clinical use. The IgG1 antibodies bind to AQP4 on the cell surface and can initiate complement deposition. These approaches will be useful for investigation of other antibody-mediated diseases.